Spinal Arteriovenous Vascular Malformations in Patients with Neural Tube Defects - Giordan, E. (AJNR Am J Neuroradiol, 2018)
BACKGROUND AND PURPOSE: Neural tube defects, such as tethered cord, intradural lipoma, or myelomeningocele may coexist with spinal vascular malformations. The coexistence of these 2 rare entities is suggestive of a causal relationship between them, which may lead to further understanding of their pathogenesis. We present a series of 6 patients with epidural spinal arteriovenous fistulas associated with neural tube defects. MATERIALS AND METHODS: We retrieved cases of spinal vascular malformations associated with neural tube defects seen at our institution. The clinical presentation, MR imaging/MRA and angiographic imaging, treatment outcomes, and long-term neurologic outcomes were analyzed. Descriptive statistical analyses are reported. RESULTS: Six patients with epidural arteriovenous fistulas and neural tube defects were included in this study. The mean age at presentation was 42 years, and the most common presenting symptoms were lower extremity weakness followed by sensory disturbances and bladder/bowel dysfunction. In most cases (5/6), the fistulas were located at the sacral level. All cases were fed by the lateral sacral artery (6/6). Four patients had prior spine surgery, but the fistula was in the operative bed in 2 cases. All fistulas were extradural with secondary intradural venous drainage. Five patients underwent transarterial embolization with Onyx, and 1 patient had a treatment-related complication. CONCLUSIONS: It is conceivable that there is a pathophysiologic link between neural tube defects and development of spinal vascular malformations. Delayed neurologic deterioration or high conus signal in a patient with a neural tube defect should suggest the possibility of such an association.